Cigarette and IL-17A synergistically induce bronchial epithelial-mesenchymal transition via activating IL-17R/NF-κB signaling - Libing Ma; Ming Jiang; Xiaoli Zhao; Jingyi Sun; Qilu Pan; Shuyuan Chu (BMC Pulmonary Medicine, 2020)
Abstract Background IL-17A directly induces epithelial-mesenchymal transition (EMT) in alveolar epithelial cells. It could coordinate with cigarette smoke extract (CSE) to promote proliferation of bronchial epithelial cells. In this study, we aim to explore the direct effect of IL-17A and CSE on EMT in bronchial epithelial cells. Methods Bronchial epithelial cells were isolated from C57BL/6 mice, and cocultured with CSE or/and IL-17A. E-cadherin and Vimentin expressions in cells were detected using immunofluorescence staining. IL-17R expression was detected using immunohistochemistry staining. NF-κB expression was assessed using western blotting. When NF-κB was inhibited by BAY 11–7821, expressions of NF-κB, E-cadherin and Vimentin were measured. Results The protein expression of E-cadherin in bronchial epithelial cells was lowest in CSE + IL-17A group, followed by CSE group. In contrast, the protein expression of Vimentin was highest in CSE + IL-17A group, followed by CSE group. Similarly, IL-17R and NF-κB expressions were highest in CSE + IL-17A group, followed by CSE group and IL-17A group. NF-κB inhibitor could inhibit the expressions of E-cadherin and Vimentin. Conclusions Cigarette and IL-17A could synergistically induce EMT in bronchial epithelial cells through activating IL17R/NF-κB signaling. Our findings contribute to a better understanding in airway EMT and pathogenesis of respiratory diseases, which are involved IL-17A and cigarette smoking. Those will provide novel avenues in the immunotherapy of lung diseases.